Opinie osób bezrobotnych na temat form przeciwdziałania bezrobociu oraz zakres korzystania z tych form w świetle badań empirycznych - Szulczyńska, Urszula; Karlińska, Wiesława (Opinions of Unemployed Persons on Forms of Countering Unemployment and Scope of Utilization of the Forms in the Light of Empirical Research, 2009)
The aim of the paper is to present the opinions of unemployed people on the methods of combating unemployment. The second objective is to present the opinion of the unemployed on the quality of services provided by the district employment office - a major institution which promotes local employment. Considerations are based on the results of survey conducted in 2008 among the unemployed in the Trzcianecko-Czarnkowski district, second district in the area of Wielkopolska.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 383-392